2012
DOI: 10.1038/cdd.2012.18
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Drp1 provides neuroprotection in vitro and in vivo

Abstract: Impaired regulation of mitochondrial dynamics, which shifts the balance towards fission, is associated with neuronal death in age-related neurodegenerative diseases, such as Alzheimer's disease or Parkinson's disease. A role for mitochondrial dynamics in acute brain injury, however, has not been elucidated to date. Here, we investigated the role of dynamin-related protein 1 (Drp1), one of the key regulators of mitochondrial fission, in neuronal cell death induced by glutamate toxicity or oxygen-glucose depriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
261
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(288 citation statements)
references
References 40 publications
20
261
0
Order By: Relevance
“…Drp1 has been put forward as a drug target for preventing mitochondrial fragmentation under diverse pathological conditions (Rosdah et al, 2016). Indeed, currently available Drp1 inhibitors have shown neuroprotective properties in animal models of HD (Guo et al, 2013b), PD (Hatch et al, 2014;Filichia et al, 2016) and ischemic stroke (Grohm et al, 2012;Li et al, 2015;Zhang et al, 2013). However, given the widespread expression of the fission enzyme and the detrimental consequences on the development and function of the nervous system upon deletion of Drp1, targeting neuron-specific regulators of Drp1 or other components of the mitochondrial fission/fusion machinery are potentially safer therapeutic strategies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drp1 has been put forward as a drug target for preventing mitochondrial fragmentation under diverse pathological conditions (Rosdah et al, 2016). Indeed, currently available Drp1 inhibitors have shown neuroprotective properties in animal models of HD (Guo et al, 2013b), PD (Hatch et al, 2014;Filichia et al, 2016) and ischemic stroke (Grohm et al, 2012;Li et al, 2015;Zhang et al, 2013). However, given the widespread expression of the fission enzyme and the detrimental consequences on the development and function of the nervous system upon deletion of Drp1, targeting neuron-specific regulators of Drp1 or other components of the mitochondrial fission/fusion machinery are potentially safer therapeutic strategies.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro models of cerebral ischemia confirm these findings, as glutamate excitotoxicity (Kumari et al, 2012;Niizuma et al, 2010) and hypoxia (Sanderson et al, 2015) on their own can induce mitochondrial fragmentation. The relationship between mitochondrial fission and ischemic injury appears more than correlative, as inhibition of Drp1 with the small-molecule inhibitor mdivi-1 was shown by several groups to decrease infarct volume following MCAO (Grohm et al, 2012;Li et al, 2015;Zhang et al, 2013). However, a number of surprising observations question the interpretation that inhibition of Drp1 protects neurons from ischemic death by preventing mitochondrial fission.…”
Section: Mitochondrial Fission In Cerebral Ischemiamentioning
confidence: 99%
“…Mdivi‐1 was reported to inhibit the activity of the mitochondrial fission regulator Drp1 and also impedes apoptosis early in the intrinsic pathway by blocking Bax/Bak‐dependent mitochondrial outer membrane permeabilization 33. Moreover, studies also showed that mdivi‐1 also blocks pro‐apoptotic Bax‐dependent cytochrome C release from isolated mitochondria33 and attenuates neural cell death in vitro and in vivo 56, 57. In the current study, we found that mdivi‐1 inhibited Drp1‐mediated mitochondrial fission, decreased Bax expression, and significantly improved mitochondrial respiration, resulting in decreased cell death induced by D7‐Des in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of cell viability or cell survival was measured using the MTT assay, MTS assay, and DAPI staining as described previously. [51][52][53] The relative reduction of MTT and MTS was quantified by measuring optical density at 560 nm using a plate reader (Bio-Tek Instruments, Winooski, VT, USA). DAPIstained cells are counted using Image-Pro Plus Version 6.0 (Media Cybernetics, Bethesda, MD, USA).…”
Section: Methodsmentioning
confidence: 99%